Libraries as Information Tourism Environments: : Unraveling T–A–P Activity Dynamics for Experience-Driven Information Services - Kayode Sunday John Dada; Romoke Opeyemi Quadir; Amina Muhammad (Indonesian Journal of Librarianship, 2026)
Background: Libraries face intensifying pressure to reconceptualise their services and spaces in response to shifting user behaviour and the emergent experience economy. Despite decades of scholarship on information-seeking behaviour, the literature still lacks a unified framework that simultaneously accounts for motivational types, purposive activities, and experiential place qualities in library encounters. Purpose: This paper introduces and empirically validates the Library T–A–P (Tourism Type–Activity–Place) framework, adapting Tongtep et al.’s T–A–P Triangle from special-interest tourism recommendation to theorise information-seeking behaviour dynamics within library environments. Method: A two-phase mixed-methods approach was employed: (1) a systematic conceptual analysis synthesising literature across library and information science, tourism studies, activity theory, and experience design, following Jabareen’s (2009) conceptual framework analysis methodology; and (2) a structured expert validation survey (n = 186 library and information professionals across 12 countries), using a 5-point Likert-scale instrument with T–A–P Coherence Scoring. Inter-rater reliability for data coding was assessed via Cohen’s kappa (κ = 0.81). Result: Eight Information Tourism Types were mapped onto a taxonomy of information activities and library place typologies. Validation confirmed strong T–A–P coherence across all categories (Grand Mean = 4.38/5.00), with Cultural Heritage Tourism (4.77) and Special-Interest Tourism (4.63) yielding highest coherence indices.  Conclusion: The Library T–A–P framework offers a theoretically grounded, triadic, activity-centred paradigm for library service design, space planning, and personalised information recommendation. While expert validation provides the framework's foundational construct validity, future empirical user studies are crucial for demand-side validation.